2007
DOI: 10.1007/s11199-006-9169-x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Physical Attractiveness, Sexual History, and Sexual Intentions: An Internet Study

Abstract: This study was designed to examine the influence a potential date's physical attractiveness and sexual history has on an individual's intentions to engage in safer sex. Over 1,200 participants completed an Internet survey. The questionnaire presented a randomized biography and photograph and asked participants to rate their interest in dating and having a sexual relationship with the target. Participants were randomly assigned to one of six conditions based on the target's physical attractiveness (low vs. high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
2
9
0
2
Order By: Relevance
“…Intention to have unprotected sex was independently reduced by the attractiveness of the potential partner, the potential partner's HIV status and sexual arousal. Similar findings have also been obtained in heterosexual men and women, with increased willingness to have unprotected sex with an attractive partner, relative to a less attractive one (Epstein et al, 2007). While these two studies did not directly ask for STI risk judgments, it is apparent that the behavioral intentions carry a heightened risk of disease transmission, and that this heightened risk is very likely to be known to the participant.…”
Section: Introductionsupporting
confidence: 71%
“…Intention to have unprotected sex was independently reduced by the attractiveness of the potential partner, the potential partner's HIV status and sexual arousal. Similar findings have also been obtained in heterosexual men and women, with increased willingness to have unprotected sex with an attractive partner, relative to a less attractive one (Epstein et al, 2007). While these two studies did not directly ask for STI risk judgments, it is apparent that the behavioral intentions carry a heightened risk of disease transmission, and that this heightened risk is very likely to be known to the participant.…”
Section: Introductionsupporting
confidence: 71%
“…However, this hypothesis is undermined by Dijkstra et al's finding 12 that participants perceived highly attractive women to be more promiscuous and more likely to have an STI than less attractive women. Conversely, Epstein et al 14 did not find a significant effect of perceived attractiveness on condomless sex intentions or perceived STI likelihood.…”
Section: Discussionmentioning
confidence: 86%
“…However, path analysis revealed that the total indirect effects of physical attractiveness on intentions to use condoms were five to six times larger than those for sexual health information about the target. More recent work by Epstein et al , 14 which involved an internet study displaying a picture and a biography for a randomly assigned target, also supported the hypothesis that a potential partner's physical attractiveness has an impact on intentions to have sex in men and women. However, no significant direct effects of physical attractiveness on intentions to have condomless sex or on perceived STI risk were found.…”
Section: Introductionmentioning
confidence: 81%
“…Stereotypic gender differences in partner preferences continued to prevail in this decade (e.g., Henningsen et al 2006;Hetsroni 2000). Men valued beauty more in choosing a partner in a hypothetical dating game (Hetsroni 2000) and expressed more interest in having sex with hypothetical partners (Epstein et al 2007). In fact, research on sexual language count that men assigned more favorable ratings to the term "feminist" than women, perhaps as the result of men considering feminists to be more liberated sexually (Noland et al 2004).…”
Section: Cultural Scriptsmentioning
confidence: 99%